V. Seseman and N. Hartmann: Friendship and Collaboration - Juršėnas, Nikodemas (Problemos, 1995)
The lives and views of the two philosophers – V. Seseman and N. Hartmann – are described. The paper is based essentially on unpublished letters of the two philosophers. The relations between N. Hartmann and his Marburgian friend H. Heimsoeth (1886-1975) are considered too. The academic situation of the time as well as philosophical schools of H. Cohen, P. Natorp, E. Husserl, W. Dilthey, A. Bergson, and M. Scheler are presented.